2003
DOI: 10.1088/0953-4075/36/4/303
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependence of non-sequential double ionization

Abstract: The frequency dependence of non-sequential double ionization (NSDI) of Ne is studied using a semiclassical rescattering model. It is found that the ratio (Ne2+/Ne+), calculated for a laser intensity of 1.0 × 1015 W cm−2, increases while the wavelength decreases down to about 250 nm, the limit of the applied model. Careful investigations of the trajectories show that there are two categories of double ionization: ‘instant ionization’ and ‘delayed ionization’. By limiting the time interval between the re-collisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Our results also showed that when the wavelength increases the yield begins to saturate and then decreases with wavelength. This behavior is in accordance with (CHEN et al, 2003, WIEHLE, 2005. In addition, our calculation clearly showed that when the ellipticity increases further value ionization yield significantly reduces.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Our results also showed that when the wavelength increases the yield begins to saturate and then decreases with wavelength. This behavior is in accordance with (CHEN et al, 2003, WIEHLE, 2005. In addition, our calculation clearly showed that when the ellipticity increases further value ionization yield significantly reduces.…”
Section: Resultssupporting
confidence: 89%
“…Additionally, lines with different ellipticities coincide with each other in the short-wavelength regime. This fact can be explained using the mechanism used to describe the frequency dependence in (CHEN et al, 2003). Our results also showed that when the wavelength increases the yield begins to saturate and then decreases with wavelength.…”
Section: Resultssupporting
confidence: 58%
“…The general behavior of the wavelength dependence is not modified much: the ratios first increase, reach a peak, and then drop with increasing wavelength. This kind of wavelength dependence of the NSDI process has been reported both for linearly and elliptically polarized laser fields in Ref [23]. As shown in Fig.…”
Section: Resultssupporting
confidence: 80%
“…And, according to the analysis in Ref. [23], in a longwavelength regime, the diffusion effect may play a dominant role. So the NSDI is suppressed for a long wavelength after taking into account nonzero initial longitudinal velocity.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation